Morphological features of larvae of Pandalus eous, P. goniurus, and P. tridents (Decapoda, Pandalidae) from planktonic samples taken in marine waters near Kamchatka Peninsula - SEDOVA, NINA; GRIGORIEV, SERGEY (Zootaxa, 2017)
Description of larvae of three species: Pandalus eous, P. goniurus and P. tridens (family Pandalidae) from planktonic samples taken in the Okhotsk Sea, Avacha Gulf, and in the Bering Sea is given. Morphological features of larvae for the purpose of their identification are compared. Features which are not subject to significant intraspecific variation, and which is useful for the separation of these species in larval period are discussed. The most important features for identification of larvae of these species may be the structure of the rostrum, the presence or absence of denticles on the carapace and abdomen, the number of setae on different legs. The most reliable feature for the separation of larvae of these species into stages of zoea is the structure of the maxilla. A key to identify of species in larval stages and drawings of separate stages are given.